Dependence on treatment ion energy of nitrogen plasma for oxygen reduction reaction of high ordered pyrolytic graphite. (1st November 2018) - Hashimoto, Yuichi; Huang, Hsin-Hui; Yoshimura, Masamichi; Hara, Masanori; Hara, Tamio; Hara, Yasuhiro; Hamagaki, Manabu
Abstract: We investigated the contribution of kinetic energy of ions on nitrogen plasma treatment of high ordered pyrolytic graphite (HOPG) film for electro-catalyst material. The treatment was carried out to modify the HOPG surface by nitrogen ion irradiation between 10 and 100 eV using electron-beam-excited plasma (EBEP). In the case of treatment by nitrogen ions with kinetic energy of 60 eV, the oxygen reduction reaction (ORR) activity was markedly improved and the ORR current increased by about 15 times as compared with untreated specimen. The enhancement of ORR activity was explained in terms of an increase of graphitic-N and pyridinic-N components, which act as reaction sites of ORR, from the results of Raman spectroscopy, X-ray photoelectron spectroscopy, low-energy photoelectron counter in air, and atomic force microscopy.